OPTIMISATION PROCEDURE OF INNER GEOMETRY IN SPHERICAL ROLLER BEARINGS WITH REGARD TO THEIR DURABILITY - Ján ŠTEININGER; Slavomír HRČEK; Lukáš SMETANKA; Rudolf SKYBA (Scientific Journal of Silesian University of Technology. Series Transport)
This article deals with an optimisation procedure of inner geometry of rolling elements designed for spherical roller bearings. A process of selection of the most appropriate solution to increase spherical roller bearing durability is understood under the term optimisation in this case. The aim of this article is to examine the impact of a change of inner geometry on the durability and reliability of spherical roller bearings regarding production technology and competitiveness. Contact strain along with a spherical roller by means of Finite Element Method (FEM) in contact points of components of a spherical roller bearing by means of designed 3D parametric models. The most appropriate shape of inner geometry of a bearing from the standpoint of calculated durability will be determined based on the results of analyses.